Investigation of the Interface of Y3Fe5O12/Gd3Ga5O12 Structure Obtained by the Liquid Phase Epitaxy. Issue 5 (20th February 2022) - Syvorotka, Ihor I.; Sugak, Dmytro; Yakhnevych, Uliana; Buryy, Oleh; Włodarczyk, Damian; Pieniążek, Agnieszka; Zhydachevskyy, Yaroslav; Levintant‐Zayonts, Neonila; Savytskyy, Hrygoryy; Bonchyk, Oleksandr; Ubizskii, Sergij; Suchocki, Andrzej
Abstract: The changes in the optical, structural, mechanical properties, and chemical composition of Y3 Fe5 O12 /Gd3 Ga5 O12 (YIG/GGG) single crystal structures grown by liquid phase epitaxy, particularly at the interface between the film (Y3 Fe5 O12 ) and the substrate (Gd3 Ga5 O12 ), are studied. Different complementary techniques, including optical microscopy, local spectrophotometry, electron probe microanalysis, micro‐Raman spectroscopy, and nanohardness analysis are used. The main finding of the study is an experimental approach, in which the probe of the measuring device (light beam, electron beam, nanoindenter) is directed to the surface of the studied sample in a direction perpendicular to the direction of structure growth, and the surface is scanned along this direction. It allows to obtain the profiles of changes in refractive properties, nanohardness, optical absorption, chemical composition, and intensity of phonon spectrum bands at the transition from the GGG to YIG. It is established that the lengths of the scanning intervals, at which the changes of various properties of a specimen occur, differ significantly. The obtained results are affected by the size of the probes and by the sensitivities of both the particular measuring method and the particular physical property of the material to changes in the chemical composition and crystalline structure of the sample. Abstract : The changes of the properties of Y3 Fe5 O12 /Gd3 Ga5 O12 single crystal structures grown by liquid phase epitaxy, particularly at the interface between the film (Y3 Fe5 O12 ) and the substrate (Gd3 Ga5 O12 ), are studied. The profiles of chemical composition, optical, structural, and mechanical properties of the structure during transition through the interface from the substrate (GGG single crystal) to the YIG epitaxial layer are obtained.